Power, Politeness, and Ideology: A Critical Discourse Analysis of the Trump-Zelenskyy Meeting in the Oval Office on February 28, 2025 - Dasko Khasro Mohammed; Nur Syuhada binti Mohd Radzi (HISTORICAL: Journal of History and Social Sciences, 2025)
This study applies a Critical Discourse Analysis (CDA) approach to examine how language constructs power, resistance, and ideological positioning in the highly publicized Oval Office meeting between Donald Trump and Volodymyr Zelenskyy on February 28, 2025. Drawing on van Dijk’s socio-cognitive model and Grice’s Cooperative Principle, the study analyzes selected exchanges from the televised interaction to uncover discursive strategies of dominance, deflection, and face negotiation. The analysis focuses on lexical choices, pragmatic violations, metaphor use, and pronoun positioning, revealing how each leader performs political identity, frames legitimacy, and navigates unequal power relations. Findings highlight how Trump's assertive lexis, coded metaphors, and interruptions reflect ideological control, while Zelenskyy’s mitigated language and pragmatic appeals reveal both resistance and vulnerability, shaped in part by his non-native English proficiency. The paper contributes to understanding how linguistic choices in real-time political talk can reinforce or disrupt power hierarchies and shape international diplomatic narratives. At the results of the study will investigate the facts that language power mostly able at determined the consequences of the political debate or conversation between two Politian leaders.